Pharyngeal pouch management: an historical review. Issue 2 (16th September 2015) - Stewart, K; Sen, P
Abstract: Background: Management of the pharyngeal pouch has evolved enormously since the first description by Ludlow in 1764 and the first case series by Zenker and Von Ziemssen in 1877. With the introduction of antibiotics, and the advancement of surgical technique with the advent of endoscopic surgery and lasers, current management is vastly different to that in the nineteenth century. Objectives: This paper traces the history of pharyngeal pouch management, and discusses the various treatment options and opinions recorded during the nineteenth and twentieth centuries, comparing these with techniques popular today. Results and conclusion: Pharyngeal pouch surgery has been associated with significant morbidity, both because of the elderly age of patients typically affected by the condition and because of the surgery itself and potential post-operative complications encountered. The historical development of pharyngeal pouch management and the understanding of pharyngeal pouch pathophysiology are discussed.